Relationship between fitness level and injury status among Pahang State female football players / Helmi Farhakim Mat Noor - Mat Noor, Helmi Farhakim (Faculty of Sport Science and Recreation, 2017)
Football really is worldwide sports that play by both male and female. There were many major big competitions such as World cup, EURO and Concacaf Cup. But all the major event only focus on male competition rather than female. Fans normally do not support female football match because of many aspect but the major of it is the feminist side of women. According (e.g., Bourke, 2003), Women's soccer, in contrast to men's soccer, has a relatively short history. This also led to short interest of researcher on the female football player. The subject is (N=20) from the Pahang FA female team. Subject age are in range (19-26). The team are currently preparing for the Liga Kebangsaan and the LBR female tournament. Three fitness test will be perform by them which is bleep test (endurance), illnois agility test (agility) and 30M sprint (speed). The result of this study found the coefficient correlation between the three fitness component and injury status of the players are moderate. The p value for two of the fitness variable that correlate with injury found it significant when 0<0,05 except for speed of the players and the injury is not significant when p>0.05. It is possible that level of the fitness of the female players do contribute in preventing the injury of the female players.